KEVALIDAN PERANGKAT PEMBELAJAAN MENGGUNAKAN MODEL OPTHREE BERBANTUAN MEDIA GOOGLE SITES PADA KONSEP FLUIDA STATIS - Mauli, Eka Nurdiana U; Supartin; Demulawa, Meilan (Anatesa : Kajian Pendidikan, Sosial dan Keagamaan, 2025)
The purpose of this study is to develop Learning Devices using the OPHThreee Model assisted by valid Google Sites media. This study is a development research (Research and Development) that adapts the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation).Data collection instruments include Expert Validation Sheets, which are carried out by two validators who have the appropriate competencies. The results of the study showed that the results of the validation of learning devices obtained an average value of the teaching module of 3.57, teaching materials of 3.50, Student Worksheets of 3.48, Learning media of 3.65, and Learning Outcome Tests of 3.51 so that they are declared valid and can be used with a little revision. Based on the results of the study, it can be interpreted that the physics learning device using the OPthree model assisted by Google Sites media on the static fluid concept that has been developed is of high quality and suitable for use in learning.